Recent diversification in the high Andes: Unveiling the evolutionary history of the Ecuadorian hillstar, Oreotrochilus chimborazo (Apodiformes: Trochilidae) - Bonaccorso, Elisa (2021)
Studying the genetic signatures of evolutionary diversification in young lineages is among the most promising approaches for unveiling the processes behind speciation. Here, we focus on Oreotrochilus chimborazo, a high Andean species of hummingbird that might have experienced rapid diversification in the recent past. To understand the evolution of this species, we generated a dataset of ten microsatellite markers and complementary data on morphometrics, plumage variation and ecological niches. We applied a series of population and coalescent-based analyses to understand the population structure and differentiation within the species, in addition to the signatures of current and historical gene flow, the location of potential contact zones and the relationships among lineages. We found that O. chimborazo comprises three genetic groups: one corresponding to subspecies O. c. chimborazo, from Chimborazo volcano and surroundings, and two corresponding to the northern and southern ranges of subspecies O. c. jamesonii, found from the extreme south of Colombia to southern Ecuador. We inferred modest levels of both contemporary and historical gene flow and proposed the location of a contact zone between lineages. Also, our coalescent-based analyses supported a rapid split among these three lineages during the mid-to-late Holocene. We discuss our results in the light of past and present potential distributions of the species, in addition to evolutionary trends seen in other Andean hummingbirds.